2015
DOI: 10.1097/sap.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Airway Obstruction and the Unilateral Cleft Lip and Palate Deformity

Abstract: In patients with unilateral CLP, the bony nasal septum can demonstrate significant deviation and airway stenosis. Surgeons should consider a bony septoplasty in their treatment algorithm in unilateral CLP patients who have reached skeletal maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 31 publications
5
44
0
Order By: Relevance
“…Although we also found lower volumes in UCLP patients than in controls, the more complete nasal cavities used here resulted in volumes that were considerably larger than those found by Aras et al despite the younger age of our subjects (7–12 vs. 13–15 years old). Friel et al reported a significant volume decrease in the affected nasal side compared to the unaffected side in UCLP patients. We also observed lower volumes on the affected side in nine of 10 UCLP patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although we also found lower volumes in UCLP patients than in controls, the more complete nasal cavities used here resulted in volumes that were considerably larger than those found by Aras et al despite the younger age of our subjects (7–12 vs. 13–15 years old). Friel et al reported a significant volume decrease in the affected nasal side compared to the unaffected side in UCLP patients. We also observed lower volumes on the affected side in nine of 10 UCLP patients.…”
Section: Discussionmentioning
confidence: 98%
“…Three prior studies used 3D reconstructions from CT scans to analyze nasal cavity volumes in patients with CLP . Aras et al presented a lower median volume in UCLP compared to controls, although they used a truncated nasal region for volume measurement resulting in median nasal volumes of 3,108.98 and 5,367.4 mm 3 in UCLP and controls, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That cleft‐side segment is more susceptible to upper lip pressure, causing it to relocate posteriorly and create overall distortion in facial bones, leading to facial asymmetry (Nagasao et al, ). These factors can result in bony asymmetry of internal airway passages that can impair nasal breathing and force an individual to breathe orally, thereby increasing suceptability to infection by bypassing the body's natural nasal air filtration system, and possibly necessitating surgical intervention to improve quality of life (Friel et al, ). Additionally, deformed regions of the craniofacial complex are often associated with reduced sinus volumes in nearby structures, reduced nasal airway volumes (Starbuck et al, ), and increased mucosal thickening of sinus walls (Kula et al, ), which also may increase likelihood of infection.…”
Section: Discussionmentioning
confidence: 99%